MAKING MULTIPLE OF MULTI-POLY CULULOSE COMPOSITE POLYCULOSE FOR SEPARATION OF TEXTILE COLOR DYES - Heru Pratomo (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2005)
The purpose of this work is, to determine the role of supportcomposite polysuljone - cellulose acetate membrane in separating textile dyes. The subject is the textile dyes, and the object is dispersing textile dyes. The solution of the textile dyes (red, yellow and blue) made as wastewater from textile industry. It can be concluded that the support composite polysuljone - cellulose acetate membrane showed good permeability and high permsefectivity in separating textile dyes.